Dampak Intellectual Capital dan CSR Terhadap Firm Value dengan Profitabilitas Sebagai Variabel Intervening - Putri, Syifa Aulia Zhara; Wafiroh, Novi Lailiyul (Politeknik Piksi Ganesha Indonesia, 2024)
Companies generally have long-term and long-term goals, the company's long-term goal is to maintain business continuity and increase company value. The purpose of this research is to find out how the components of intellectual capital such as VAHU, STVA and VACA influence firm value with profitability as a variable. intervening in technology and telecommunications sector companies listed on the BEI for the period 2020 – 2022. The research method uses quantitative and uses panel data analysis through the e-views 12 application. The results of this research state that VAHU, STVA, VACA and CSR have a simultaneous effect on profitability but have no effect on firm value, and profitability is able to mediate VAHU, STVA and CSR on Firm Value..